Pengambilan Keputusan Petani Jagung (Zea Mays L.) Terhadap Penentuan Sistem Penjualan dalam Menghadapi Dampak Perubahan Iklim - M. Fahrul Rizal; Nurul Fathiyah Fauzi; Retno Murwanti (Universitas Khairun, 2026)
Climate change is one of the challenges in corn farming because it causes uncertainty in planting seasons, production fluctuations, and changes in selling prices that influence farmers' decisions in determining the sales system of their harvest. This study aims to analyze the impact of climate change on farmers' decision-making in corn sales systems, changes in corn production and selling prices, and factors that influence farmers' decisions in determining sales systems in the 2nd and 3rd planting seasons. The study was conducted at the Rambutan Jaya Farmers Group, Bangsalsari District, Jember Regency, using descriptive and analytical methods with a multinomial logistic regression approach. The research sample was determined by purposive sampling of 44 corn farmers. The results showed that the sales system of corn kernels was the main choice of farmers, amounting to 77.27% in the 2nd planting season and increasing to 84.09% in the 3rd planting season because it is more practical, accelerates income receipts, and reduces post-harvest risks. Average corn production increased from 4.7 tons to 6.0 tons, while the selling price increased from Rp2,945/kg to Rp3,386/kg. The results of the multinomial logistic regression analysis indicate that climate variables significantly influenced farmers' decisions in the third planting season, while selling price did not. This study demonstrates that farmers' decisions regarding sales systems are influenced not only by climate conditions and selling prices, but also by considerations of efficiency, ease of marketing, and efforts to minimize risk.